Enhancement of Eu3+ emission in solution by bulky chelating ligands and deuterium substitution. Issue 1 (2002) - Zaitoun Zaitoun, Mohammed A. Mohammed A.
Abstract : Binding the europium ion with a bulky chelating ligand provides one strategy for minimizing the quenching effects of water on the luminescence of the ion. 1, 4, 8, 11-tetraazacyclotetradecane-1, 4, 8, 11-tetraaceticacid tetrahydrochloride (TTT) was used as a chelating agent to isolate Eu 3+ from hydroxyl deactivation in water. A large enhancement in the Eu 3+ emission was observed for the chelated Eu 3+ compared to the unchelated. Absorption and emission spectra are reported together with lifetime measurements. The latter were used to study concentration quenching and quenching by water.